SERUAN NABI IBRAHIM TERHADAP KAUMNYA DALAM MENANAMKAN AQIDAH TAUHID DALAM SURAT AL-AN’AM AYAT 74-79 - Ummu Safiah Binti Che Mat; APRYANTI APRYANTI (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This article shows the call of Prophet Ibrahim to his people in cultivating the belief of monotheism through natural phenomena found in Surat al-An‘am verses 74-79. This letter talks about the efforts of Prophet Ibrâhîm in inculcating the monotheistic beliefs of his father and his people who worshiped idols and worshiped the stars, moon and sun. Where what was conveyed by Prophet Ibrahim that is contained in his mind is a strong belief and trust from the guidance of Allah swt. The verse also tells about Prophet Ibrahim, where at that time Prophet Ibrahim made the stars, moon and sun as a medium to tell his people that the stars, moon and sun are God's creation and not the god they believe in. Prophet Ibrahim lived in an environment of worshipers of the stars, moons and stars. He educated his people by adapting and adapting to the level of understanding and knowledge so that his people believed in piety to the god of the universe, Allah swt. Then he accompanied his people towards true I'tikad step by step. That is why Prophet Ibrahim when he saw the star appear, Prophet Ibrahim said